2022
DOI: 10.1097/shk.0000000000002007
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Myeloid-Derived Suppressor Cell Expansion After Cardiac Surgery With Cardiopulmonary Bypass Induces Lymphocyte Dysfunction

Abstract: Cardiac surgery with cardiopulmonary bypass (CPB) is associated with an immune paresis that predisposes to the development of postoperative infections and sepsis. Among factors responsible for CPB-induced immunosuppression, circulating myeloid-derived suppressor cells (MDSCs) have been found to induce early lymphocyte apoptosis and lymphocyte proliferation inhibition. However, the mechanisms involved are not fully understood. In this study, we found that the main lymphocyte subsets decreased significantly 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Comparative data to other studies investigating IDO activity in cardiac surgery patients remain scarce. A study investigating immune suppression following CPB in 43 adult patients found higher IDO levels postoperatively than preoperatively, indicating a T-cell dysfunction; however, the addition of an IDO inhibitor ex vivo showed no benefit [ 26 ]. Sabapathy et al conducted a study in 2021 involving 51 infants aged 31 days to 2 years undergoing CPB surgery for single-ventricle heart disease (SVHD).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative data to other studies investigating IDO activity in cardiac surgery patients remain scarce. A study investigating immune suppression following CPB in 43 adult patients found higher IDO levels postoperatively than preoperatively, indicating a T-cell dysfunction; however, the addition of an IDO inhibitor ex vivo showed no benefit [ 26 ]. Sabapathy et al conducted a study in 2021 involving 51 infants aged 31 days to 2 years undergoing CPB surgery for single-ventricle heart disease (SVHD).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac surgery with the use of cardiopulmonary bypass (CBP) is another externally induced condition which triggers massive systemic inflammation by activating inflammatory leukocytes due to high shear stress, potentially leading to a prolonged hospital stay and multiorgan dysfunction [ 25 ]. Moreover, there is evidence that CPB results in postoperative immunosuppression due to induced lymphocyte dysfunction, leading to an increased susceptibility to infections [ 26 ]. This immune response is fueled by multiple factors such as the surgical trauma itself, blood interaction with extracorporeal circuits, and reperfusion injury [ 27 ], and has repeatedly been shown to influence postoperative outcomes [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoparalysis represents impaired immune defence, which is regarded as the outcome of an exaggerated or prolonged anti-inflammatory response after CPB and is considered relevant to the IL-10 genotype [ 72 , 73 ], and peroxiredoxin-1, a cytosolic antioxidant released during CPB, can induce phagocytes to produce IL-10 via Toll-like receptor (TLR) 4 [ 74 ]. The latest study showed that increased monocytic myeloid-derived suppressor cells and insufficient L-arginine might also be responsible for postoperative immunoparalysis [ 75 ], and cell population data, consisting of leukocyte size, granularity, and fluorescence intensity, are strongly associated with CPB and might be suitable for monitoring the activation of immunity [ 76 ].…”
Section: Pathology Mechanismmentioning
confidence: 99%
“…As mentioned above, immunoparalysis after CPB has been widely recognized, and investigations have indicated that increased catabolism of arginine might be a potential mechanism [ 223 ]. Additionally, exogenous supplementation with L-arginine successfully rehabilitates the proliferative ability of T cells in vitro [ 75 ] and is likely to lead to the development of an economical and effective hedge to reduce postoperative infection risk and the necessity of implementing nephrotoxic antibiotics.…”
Section: Medical Therapymentioning
confidence: 99%